Nomenclature history and typification of Phacelurus speciosus (Poaceae) with a new synonym - Chorghe, Alok R.; Patil, Sameer C. (Phytotaxa, 2021)
Nomenclature history related to the name Phacelurus speciosus has been discussed here. In absence of any original material a neotype is designated for the name P. speciosus. Additionally, the newly described species Rottboellia husainii is treated as a synonym of Phacelurus speciosus.